Horseshoe crab as fishery commodity in Malaysia: present and future conservation strategies - Kassim, Zaleha; Ismail, Ahmad (2018)
Horseshoe crab is a classic arthropod animal being popular dish in many Asia countries. At the same time, it is also known as living fossil due to the unchanged features since their first existence hundred millions years ago. The high demand for consumption and other exploitation purposes in the Southeast Asian region emerges issues on the efforts and conservation needs. The three Asian horseshoe crabs, Tachypleus tridentatus, Tachypleus gigas and Carcinoscopius rotundicauda are found to land and nesting in the coastal water of Malaysia. They become delicacy in sea food restaurant in some states such as Johor and Melaka. Thousands of them are caught and sent to the neighbor country, Thailand, for consumption. The animals are still recorded as ‘data deficient’ due to the lack of information on the landing status in the country. To protect the animals from over-exploitation activities which lead to extinction in the long run, concerted effort must be initiated which will involve participation of different levels of technical agencies, local communities and other stakeholders. Programs and initiatives should be targeted to the groups which directly encounter with horseshoe crabs in their daily activity, to those gained economic benefits from the animal and to those involve in managing the coastal ecosystem. Long-term data collection and updates of information would change the biodiversity and protection status of this animal. There will be a need to balance the exploitation level by protecting their natural nesting grounds on beaches along our coast and establishing sanctuaries to increase the survival rate of trilobites. Eco-educational program could be the best strategy to help maintaining the existence of horseshoe crabs in Malaysia water. At the same time, strengthening the enforcement of ocean laws and policies would help us to protect this resource.